2008
DOI: 10.1080/03602550701815979
|View full text |Cite
|
Sign up to set email alerts
|

Crush Behavior of Conical Composite Shells: Effect of Cone Angle and Diameter/Wall Thickness Ratio

Abstract: The crush behavior of truncated, conical, foam-filled, empty shells subjected to quasi-static axial crushing is investigated experimentally. Epoxy resin/E-glass shells with cone angles of 0 , 11 , and 22 and with three different diameter-wall thickness ratios were tested. Polyurethane foam with a density of 55 kg/m 3 was used in filled specimens. For empty shells showing an unstable failure mode, energy absorption was increased with the cone angle. In contrast, foam-filled shells showed a stable progressive cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Wu and Chiu [189] picked up the problem of thermoelastic buckling of laminated conical shells. Rezadoust et al [190] investigated the crush behavior of conical composite shells. Goldfeld et al [191] presented design and optimization of laminated conical shells for buckling.…”
Section: Shell Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and Chiu [189] picked up the problem of thermoelastic buckling of laminated conical shells. Rezadoust et al [190] investigated the crush behavior of conical composite shells. Goldfeld et al [191] presented design and optimization of laminated conical shells for buckling.…”
Section: Shell Geometriesmentioning
confidence: 99%
“…Other studies on failure of composite shells include those of Galishin [232], Xie and Biggers [233], He and Hwang [197], Khoroshun et al [99,100], Khoroshun and Babich [108,114,163,245], Mahdi et al [184], Rezadoust [190], Saleh et al [199], Solaimurugan and Velmurugan [169], and Ghosh [238].…”
Section: Failure Delamination and Damage Analysesmentioning
confidence: 99%
“…Substantial research efforts have been made by various experimental [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], analytical analyses [1,11,13,16] and numerical methods [3,6,7,9,12,15,[17][18][19][20]. These literatures demonstrated that foam indeed is a class of ideal materials for energy absorption because they can undergo large deformation at nearly constant load.…”
Section: Introductionmentioning
confidence: 99%
“…Huge research efforts have been carried out by various experiments (Gupta and Velmurugan, 1999;Hassen et al, 2000; Santosa et al, 2000;Borvik et al, 2003;Meguid et al, 2004;Babbage and Mallick 2005;Mamalis et al, 2008;Rezadoust et al, 2008;Taher et al, 2009;Ghamarian et al 2011;Niknejad et al, 2011;Kavi et al 2006;Seitzberger et al, 1997), analytical analyses (Gupta and Velmurugan, 1999;Taher et al, 2009;Wang et al, 2007), and numerical methods (Santosa et al, 2000;Babbage and Mallick 2005;Rezadoust et al, 2008;Niknejad et al, 20113;Seitzberger et al, 1997;Ahmad et al, 2008Ziaei-Rad et al 2008;Santosa et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%